(untitled) - Eckel, Bruce (New Jersey, 2000)
Introduces all the basics of objects as Java uses them; then walks carefully through the fundamentals of Java programming, including program flow, initialization and cleanup, implementation hiding, reusing classes and polymorphism
Lập trình hướng đối tượng
Keywords: Java (Ngôn ngữ lập trình máy tính),Object-oriented programming (Computer science),Java (Computer program language),Lập trình hướng đối tượng (Khoa học máy tính),Lập trình hướng đối tượng (Khoa học máy tính)